Analysts’ reinitiations of coverage and market underreaction - Philippot, Aurélien (Journal of Banking & Finance, 2018)
I study the informativeness of reinitiations of coverage, which are defined as the resumption of coverage of a stock by a broker after more than six months of interruption. Reinitiations are associated with a significant short-term market response, in particular when the same analyst is assigned to the stock. However, I show that this market response is incomplete. Interestingly, the price patterns that follow the issuance of regular upgrades of recommendation and reinitiations differ significantly. Prices adjust quickly after a regular upgrade, while reinitiations are followed by a sustained price increase in the following six months, which does not revert during the following two years. I assess the economic magnitude of this initial underreaction by setting up a trading strategy. I show that reinitiations of coverage are the only type of recommendation that delivers significant positive abnormal returns after transaction costs with a three- and six-month investment horizon. I study and reject several candidate explanations in relation to momentum, and PEAD. Then, I investigate an information/superior ability hypothesis. I find that reinitiations are a more accurate signal than other recommendation types. Besides, the earnings conference call transcripts show that those analysts were able to maintain active relationships with the firms, even during the interruption of coverage. Their activity level is associated with more informative reinitiations of coverage. In particular, their participation rank in conference calls, which can be seen as a proxy for ability and proximity to the management appears to be a strong predictor of the drift after the reinitiation takes place.